International Investment of Capital - McCloy, John. J. (World Bank, Washington, DC, 2019)
John. J. McCloy, President of the International Bank for Reconstruction and Development, spoke about directing international investment of capital toward productive purposes. He spoke on the role of the Bank as one of the principal international financing agencies in the world. The Bank serves as a channel of private investment funds at reasonable cost for the restoration and development of capital-importing countries. The Bank forms a safe bridge for the movement of capital. The Bank must sell securities in the private market, primarily in the United States, to raise much of the money it lends. The Bank is also in a position to supervise the spending of the loan proceeds to prevent excess borrowing. He concluded by saying that Bank can't and won't grant loans in order to accomplish political objectives or where political uncertainties make lending unsound.